On the Study Sociolinguistic Analysis of Judical Speech (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article discusses and illuminates the sociolinguistic analysis of Court Speech. Language and thinking, language and society, language and culture relations today are engaged in the study of problems in linguistics, such as psycholinguistics, sociolinguistics, pragmalinguistics, lingvocultrology, cognitive linguistics and their interdependent relationship. Unlike systemic linguistics, the fact that speech activity is the most important object of linguistic research, which has become a prelude to new perspectives, new interpretations, leads to the emergence of topical scientific problems and views as linguistics develops. In this sense, the study of the speech phenomena of linguistic units in linguistics in the sociolinguistic direction, the study of the state of speech in relation to social status, provided an opportunity to conduct sociolinguistic research in Uzbek linguistics. According to Professor Mahmudov, the direction of sociolinguistics in world linguistics, or rather the science, has emerged as a result of a comprehensive understanding of the strong connection between language and society, the understanding of the many intersecting points of linguistics and sociology The above issues are covered in the article.